SPEECH FUNCTION OF SELECTED TOPICS IN THE FIRST 2020 AMERICAN PRESIDENTIAL DEBATE. - Mogi, Maria A; Sama, Gratiana; Kasimo, Yulius Y (Lantern: Journal of Language and Literature, 2025)
The purposes of this research were to determine, describe, and find out the types of speech functions based on Halliday theory which is used by speakers, especially the candidates and the moderator in the first 2020 American presidential debate. This research used qualitative and quantitative descriptive research, and video observation method. Data were taken from the utterances produced by chosen sample data from three topics selected of the debate. The result shows that the candidates and the moderator use all types of speech function; initial and response, which is counted using the formula by Sudijono. The most frequent type of initial speech function is statement, and the response is contradiction. In a debate, the function of statement and contradiction is used to defend the argument.